The comparison of the efficacy of therapy based on acceptance and commitment and schema therapy on body image flexibility of the body and impulsivity among women with Binge eating disorder - Ostadian Khani, Zahra; Hassani, Fariba; Sepahmansour, Mojgan; Keshavarzi Arshadi, Farnaz (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the efficacy of therapy based on acceptance and commitment and schema therapy on body image flexibility and impulsivity among women with binge eating disorder. Methods: The research design was quasi-experimental with a pretest-posttest design, and a two-month follow-up. The study population included all women with binge eating disorders referring to nutrition clinics in Qom in 2018 and met the inclusion criteria of the study. The sample included 45 women with binge eating disorders who were selected by purposive sampling method and randomly assigned to two experimental and control groups (15 women in each group). The experimental group received Bach and Morgan’s (2012) treatment package based on acceptance and commitment and the Young et al.’s schema therapy package (2015) in twelve sessions, and each session lasted two hours. The research tools included the eating disorder scale of Stice, Telch, and Rizoi (2000), the flexibility of the mental image of the body of Sandoz, Wilson, Marvin, and Kate Klum (2013), and the impulsivity of Bart (2014). The data were analyzed by repeated-measures analysis of variance. Results: The findings indicated the impact of treatment based on acceptance and schema therapy on the score of mental image flexibility (F = 4.31, P = 0.020) and impulsivity (F = 6.73, P = 0.020). And this effect was stable in the follow-up stage. Besides, according to the results of the two-by-two comparison and Tukey post hoc test, it was indicated that there is no significant difference between the effects of the two therapies. Conclusions: The therapy based on acceptance and commitment is more effective than schema therapy in psychological flexibility of mental body image, anxiety, and motor impulsivity.